Comparative Analysis of Nickel–Titanium Instrumentation Systems for Root Canal Anatomy Preservation: An In Vitro Study - Eszter Nagy; Niki Kotaki; Máté Dudás; Dániel Gerhard Gryschka; Gábor Braunitzer; Mark Adam Antal (Applied Sciences)
This study aimed to evaluate the efficacy of various nickel–titanium (Ni-Ti) root canal instrumentation systems in preserving root canal anatomy, focusing on their capacity to limit changes in canal angulation. One hundred canals in fifty extracted human molars were prepared with different techniques: Step-Back, Reciproc, MTwo, ProTaper Universal (PTU), and ProTaper Next (PTN). The curvature of each canal was measured before and after treatment using Schneider’s methodology, a widely accepted method for assessing canal curvature. Descriptive and statistical analyses, including the Kruskal–Wallis test, were employed to compare angular changes across the systems. The results indicated that all techniques effectively reduced canal curvature, with each system exhibiting a reduction in mean canal angle after instrumentation. Although the Reciproc system showed the smallest mean change in angulation, no statistically significant differences were identified between any of the systems (p = 0.182). This finding suggests that while minor differences in performance may exist, they do not translate into clinically meaningful distinctions in preserving root canal anatomy. The Reciproc system’s slight advantage aligns with other studies, highlighting its conservative design and minimal dentinal stress; however, its superiority was not statistically validated in this study. The results suggest that all five systems are clinically comparable in preserving root canal anatomy, highlighting that dentists can choose from these widely available techniques without compromising anatomical preservation. While this study had limitations, including a relatively small sample size and an in vitro design, it aligns with previous findings on the mechanical behavior of Ni-Ti systems in endodontic practice.